Pengembangan Media Pop Up Book Digital Berbasis Open Ended Problem Terhadap Kemampuan Pemahaman Konsep Matematis dalam Materi Bangun Ruang pada Siswa Kelas VII SMP Negeri 9 Sungai Raya - Ananda, Fadila Dwi; Saputro, Marhadi; Irvandi, Wandra (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to develop a digital Pop Up Book learning medium based on Open Ended Problems to improve students' mathematical concept comprehension skills in the subject of cubes in Grade VII at SMP Negeri 9 Sungai Raya. The method used is Research and Development (R&D) with a 4D model modified into three stages, namely Define, Design, and Develop. Research data was obtained through validation by subject matter experts, media experts, and language experts, as well as through questionnaires for teachers and students and learning outcome tests. Data analysis was conducted using descriptive quantitative and qualitative methods. Validation data was analysed using percentages to assess the validity of the media, while practicality was determined based on the responses of teachers and students regarding the ease of use and attractiveness of the media. The effectiveness of the media was measured by comparing the average pretest and posttest scores to see the improvement in students' understanding of mathematical concepts. The results of the study indicate that the Open Ended Problem-based digital Pop Up Book is highly valid in terms of content, appearance, and language, and is considered practical and easy to use in the learning process. In addition, this media has been proven to be effective in improving students' understanding of cube concepts through open-ended problem-solving activities that stimulate critical and creative thinking. Thus, this media is suitable for use as an innovative alternative in interactive mathematics learning in junior high schools